2019
DOI: 10.4103/ija.ija_490_19
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and respiratory physiology in children

Abstract: Children are at increased risk of perioperative respiratory and cardiovascular complications because of their unique respiratory and cardiovascular physiology compared to adults. Anaesthesia can exaggerate respiratory deterioration in young children because of their inability to control respiration and inherent susceptibility to rapid desaturation, airway obstruction, early respiratory fatigue and lung atelectasis. Premature infants (less than 60 weeks of postconceptional age) can be exposed to the danger of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 26 publications
1
45
0
2
Order By: Relevance
“…The cohort RRs also indicated that lung cancer burden of younger generations in APE was higher than that in HPE. Compared with adults, due to small airway size, immature detoxi cation and metabolic system, children are more sensitive to ambient PM2.5 exposure [24].In order to prevent children from being affected by PM2.5 for a long time, we should pay attention to protection for them. For male, the APE levels of the related indicators exceed the HPE levels at earlier age (45-49).…”
Section: Discussionmentioning
confidence: 99%
“…The cohort RRs also indicated that lung cancer burden of younger generations in APE was higher than that in HPE. Compared with adults, due to small airway size, immature detoxi cation and metabolic system, children are more sensitive to ambient PM2.5 exposure [24].In order to prevent children from being affected by PM2.5 for a long time, we should pay attention to protection for them. For male, the APE levels of the related indicators exceed the HPE levels at earlier age (45-49).…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de que la inducción inhalatoria es la técnica más utilizada en la población pediátrica, existe la posibilidad de generación de gotas y aerosoles, por lo que la inducción intravenosa es preferida (12,13) , la inducción de secuencia rápida y la secuencia modificada son útiles; sin embargo, existe la posibilidad de una hipoxemia severa en pacientes pequeños, hay que recordar que en neonatos y lactantes existen factores fisiológicos que deben considerarse sumado a las diferencias anatómicas de la vía aérea superior, como un desarrollo de la musculatura intercostal y mayor dependencia del diafragma, costillas horizontalizadas y menor capacidad residual funcional, mayor volumen de cierre y un consumo metabólico de oxígeno más elevado (14) . Los pacientes con patología pulmonar también pueden manifestar hipoxemia, de tal modo que estos pacientes recibirán una ventilación suave hasta elevar la jaula torácica mientras se mantiene un sellado de la mascarilla (técnica con dos anestesiólogos) (12) .…”
Section: La Técnica Anestésicaunclassified
“…La ventilación por mascarilla, la succión y la lucha durante el proceso de intubación y extubación pueden producir aerosoles. Guo referido por Hirota (15) reportan la distribución del virus en el quirófano al colectar muestras detectadas en el aire a cuatro metros de los pacientes con COVID-19 (14) , de ahí la importancia de tener cuidado al momento de la ventilación, la relajación neuromuscular profunda es recomendable (13) y el uso de barreras antes de la instrumentación como se encuentra descrito en las distintas guías de manejo (10,12) .…”
Section: Infección Críticaunclassified
“…These include a small-sized mouth and airway, disproportionately large tongue, large head and occiput, larynx placed high in the neck and an omega-shaped epiglottis. [11] The low pulmonary reserve, high oxygen demand, limited visibility and space in the oral cavity make the management of the neonatal airway even more challenging. [11] The success rate with neonatal intubation varies from 64% with experienced providers to 20%–26% with novice providers and residents.…”
mentioning
confidence: 99%
“…[11] The low pulmonary reserve, high oxygen demand, limited visibility and space in the oral cavity make the management of the neonatal airway even more challenging. [11] The success rate with neonatal intubation varies from 64% with experienced providers to 20%–26% with novice providers and residents. [12] The margin of error with neonatal intubations is very narrow, making training extremely difficult.…”
mentioning
confidence: 99%